(untitled) (Iranian Journal of Kidney Diseases, 2013)
We present a rare complication of transplant renal artery stenting in a patient who developed subcapsular hematoma and presented as acute page kidney. We discuss possible mechanisms and successful novel management using radiological-assisted decompression. We propose considering this alternative option before proceeding with surgical exploration and renal capsulotomy.